Jellyfish and Polyps (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Marine Drugs gathers recent investigations on the proteomes, metabolomes, transcriptomes, and the associated microbiomes of marine jellyfish and polyps, including bioactivity studies of their compounds and more generally, on their biotechnological potential, witnessing the increasingly recognized importance of Cnidaria as a largely untapped Blue Growth resource for new drug discovery. These researches evoke the outstanding ecological importance of cnidarians in marine ecosystems worldwide, calling for a global monitoring and conservation of marine biodiversity, so that the biotechnological exploitation of marine living resources will be carried out to conserve and sustainably use the natural capital of the oceans.